Stability of Dichanthium annulatum for Fodder Production in Semi- Arid Rajasthan - Roy, P K; Yadav, M S; Mauria, S (Annals of Arid Zone, 2016)
Sixteen genotypes of Dichanthium annulantum were evaluated for fodder production over 4 years of growth in semi-arid Rajasthan. Stability analysis revealed significant differences between genotypes and environments (years) for green fodder and dry mailer yields. Genotype x environment (linear) component and pooled deviations were also significant for both the attributes. CAZRl 487 was found to be the most stable genotype combining high fodder potential and low mortality rate. CAZRl 491 was suitable for favourable environment.